Pragmatic Ability Deficit in Schizophrenia and Associated Theory of Mind and Executive Function - Li, Xiaoming; Hu, Die; Deng, Wenrui; Tao, Qian; Hu, Ying; Yang, Xiaoxue; Wang, Zheng; Tao, Rui; Yang, Lizhuang; Zhang, Xiaochu (Frontiers in Psychology, 2017)
Deficits in pragmatic abilities have frequently been observed in patients with schizophrenia. The objective of the study was to investigate the relationship between pragmatic deficits, ToM deficits and executive dysfunctions in schizophrenia. A group of 42 schizophrenic patients and 42 healthy controls were assessed on irony task (one type of pragmatic language), two subcomponents of ToM (cognitive, affective), and three subcomponents of EF (inhibition, updating and switching). The clinical symptoms in schizophrenia were assessed using the Positive and Negative Symptoms of Schizophrenia. The schizophrenia group exhibited significant impairments in all above tasks compared to the control group. Correlation results found that irony scores were correlated with the two subcomponents of ToM and two of the three subcomponents of EF (inhibition and updating). The regression analysis revealed that the cognitive ToM and inhibition predicted 9.2% and 29.9% of the variance of irony comprehension in the patient group, and inhibition was the best predictor for performance on irony task. Irony understanding was related to positive symptoms, but not to negative symptoms. The results suggest that the ability to interpret pragmatic language depends on schizophrenic patients’ ability to infer mental states and the ability of inhibition. It provides empirical evidence for a particular target of inhibition for rehabilitation and intervention programs developed for schizophrenic patients.